The Effect of Smartboard Use on Students’ Learning Interest in Islamic Religious Education at Grade VI of SD Negeri Mekarmanah - Siti Nurhalimah; Dera Nugraha; Alfa Rohmatin (PT. Nawa Edukasi Nusantara, 2026)
This study aims to examine the effect of Smartboard use on students’ learning interest in Islamic Religious Education among sixth-grade students at SD Negeri Mekarmanah. The study was conducted because learning interest in Islamic Religious Education still needed improvement, while the available Smartboard facility had not been used optimally in classroom learning. This research used a quantitative approach with a pre-experimental one group pretest-posttest design. The participants were 33 sixth-grade students selected through total sampling. Data were collected using a learning interest questionnaire, observation, and documentation. The questionnaire consisted of 12 valid items and showed acceptable reliability with a Cronbach’s Alpha value of 0.739. The data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the Paired Sample t-Test. The results showed that the mean score increased from 40.03 in the pretest to 50.00 in the posttest. The hypothesis test showed a significant difference between pretest and posttest scores, t(32) = -16.821, p < .001. These findings indicate that Smartboard use can improve students’ attention, interest, and active involvement in Islamic Religious Education learning.